Moderasi Kemampuan Teknik Personal dan Pelatihan terhadap Pengaruh Kecanggihan Teknologi pada Efektivitas Penggunaan SIA - Notiasih, Nyoman; Putra, I Made Pande Dwiana (E-Jurnal Akuntansi, 2021)
This study aims to empirically test the moderation of personal technical skills and training on the effect of technological sophistication on the effectiveness of the use of accounting information systems. The sample used is non-probability sampling, namely purposive sampling method using 100 respondents of employees and managers in the accounting department using SIA for more than one year. The data analysis technique used the Moderated Regression Analysis (MRA) test. Resulting in an analysis that the ability of personal engineering is able to moderate the effect of technological sophistication on the effectiveness of the use of SIA, training is able to moderate the effect of technological sophistication on the effectiveness of the use of SIA and technological sophistication has a positive effect on the effectiveness of using SIA. Keywords: Personal Technical Ability; Training; Technological Sophistication; Using SIA.